IQBAL’S EDUCATIONAL THOUGHTS AND OUR CURRENT EDUCATION SYSTEM - Dr.Mutahir Shah; Dr.Nasrin Amin; Qamar Abbas Alvi; Dr.Muhammad Said Ali; Dr.Sadaf Fatima; Shah Hussain; Dr.Muhammad Rahman; Dr.Subhanullah (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2023)
Allama Iqbal is a prominent philosopher of the Muslim nation. His ideas have a unique importance regarding the guidance of the country and the nation. He always promoted such educational ideas which are necessary for the development of the nation. Iqbal is influenced by the educational ideas of Muslim thinkers. Al-Farabi, Abu-al-Qasim, Bayezid and Maulana Room included the great philosophers. These scholars put the Muslim nation on a path of development that was the most unique. Thus, Muslims continued to rule the whole world. The reason was they were following the same teachings that were the guarantee of success and rule. For this reason, the Muslim nation remained a prominent model for the nations of the world for a long time. These traditions of this nation’s glorious past are mentioned in abundance in Iqbal’s poetic and prose works. This is the reason why Iqbal advises the Muslim nation to implement the wonderful traditions of the past. In the present article, an analytical study of the same educational ideas of Iqbal is presented.